Complications and mortality following surgery for oral cavity cancer: Analysis of 408 cases. (9th June 2015) - Schwam, Zachary G.; Sosa, Julie A.; Roman, Sanziana; Judson, Benjamin L.
<x xml:space="preserve">Abstract</x> Objectives To analyze the postoperative complications and mortality for oral cavity cancers, their time course, and to identify modifiable risk factors associated with their occurrence. Study Design Retrospective cohort study. Methods Patients undergoing surgery for oral cavity cancer were identified in the American College of Surgeons National Surgical Quality Improvement Program Participant Use Data File (2005–2010). Overall and disease‐specific complication and mortality data were analyzed using chi‐square and multivariate regression analysis. Results There were 408 cases identified. The overall 30‐day complication and mortality rates were 20.3% and 1.0%, respectively. The most common adverse events were reoperation (9.6%), infectious (6.6%), and respiratory (5.1%) complications. Twenty patients (4.9%) experienced postdischarge complications. Fifty‐two percent of postdischarge wound dehiscences and 67% of postdischarge surgical‐site infections occurred by postdischarge day 7, and 91% of all postdischarge complications occurred by postdischarge day 14. Smoking was independently associated with respiratory (odds ratio [OR] 3.59, P = .008) and surgical site complications (OR 5.13, P =.004). Neck dissection was independently associated with respiratory (OR 6.17, P = .001), surgical site (OR 6.30, P = .003), and infectious (OR 3.83, P = .003) complications. Conclusion Current smokers and those undergoing neck dissection are at high risk of postoperative complications after oral cavity cancer surgery. Less than 5% of patients experienced postdischarge complications, nearly all of which occurred by postdischarge day 14. Most early postdischarge complications occurred at the surgical site. In order to mitigate postdischarge complications and their sequelae, early clinical follow‐up should be sought for high‐risk patients. Level of Evidence 4. Laryngoscope, 125:1869–1873, 2015